Baking Master VR: The Development of a Virtual Reality (VR) Learning Application for Catering Students - LAU, QIAN WEN; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2024)
The Faculty of Technical and Vocational Education (FPTV) in UTHM offered the Bachelor Degree in Vocational Education (Catering) with Honours. FPTV catering students do not yet have VR-based learning application. Due to Covid-19 pandemic MCO and flash floods, they are forced to conduct online classes instead of physical classes. This may lead to inconvenient to learn the catering by lecture slides and imagination only. Therefore, it is to design “Baking Master VR” based on virtual reality approach, to develop the VR learning application by integrating Unity Game Engine, to perform functionality and usability testing to the target user. The Agile methodology will be used in this project to make certain that the learning application is created as scheduled. According to the Acceptability Ranges score scale, the average score of 70.00 falls within the "acceptable" range of the proposed VR application.